Examining the ordoliberal tradition in classical liberal thought - Lars P. Feld; Daniel Nientiedt (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2023)
Writing in 1951, Friedrich Hayek identified four places where the classical liberal tradition1 had been upheld and developed during the first half of the 20th century. He named London, Vienna, Chicago, and, perhaps surprising to some, the small southern German town of Freiburg (Hayek, 1951/1967). The reason for including Freiburg was that it is the birthplace of ordoliberalism, a branch of classical liberalism that to this day remains relatively unknown outside of Germany. The historical significance of ordoliberalism derives from its central role in redefining classical liberalism, and from its impact on economic policy. Representatives of ordoliberalism were key members of the neoliberal movement of the 1930s and 1940s, participating in the Lippmann Colloquium of 1938 and helping to create the Mont Pèlerin Society after WWII. In terms of economic policy, ordoliberal ideas informed the post-war creation of Germany's free-market system - the Social Market Economy - as well as certain aspects of the architecture of the European Union. (...)
Keywords: 330